2019
DOI: 10.1007/s10456-019-09688-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-derived WNT2 increases tumor angiogenesis in colon cancer

Abstract: WNT2 acts as a pro-angiogenic factor in placental vascularization and increases angiogenesis in liver sinusoidal endothelial cells (ECs) and other ECs. Increased WNT2 expression is detectable in many carcinomas and participates in tumor progression. In human colorectal cancer (CRC), WNT2 is selectively elevated in cancer-associated fibroblasts (CAFs), leading to increased invasion and metastasis. However, if there is a role for WNT2 in colon cancer, angiogenesis was not addressed so far. We demonstrate that WN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(165 citation statements)
references
References 71 publications
2
160
1
2
Order By: Relevance
“…Next, WNT2, a secreted glycoprotein, was predicted to be a potential target gene of miR-30a-3p by bioinformatics analysis. It has been reported that WNT2 can promote the development of tumors [42][43][44], and the WNT2/β-Catenin signaling pathway is related to the malignant biological functions of GC [45][46][47]. This protein drew our attention.…”
Section: Discussionmentioning
confidence: 99%
“…Next, WNT2, a secreted glycoprotein, was predicted to be a potential target gene of miR-30a-3p by bioinformatics analysis. It has been reported that WNT2 can promote the development of tumors [42][43][44], and the WNT2/β-Catenin signaling pathway is related to the malignant biological functions of GC [45][46][47]. This protein drew our attention.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple classes of molecules, including growth factors, cytokines, proteases, and extracellular matrix proteins, carried by CAF-EV mediate stroma-tumour-cell interaction [61]. Several studies sustain the role of EV derived from CAF primary cell lines on tumour proliferation, survival, migration, and invasion [62,63]. A significant role of CAF-EV in promoting the migration and invasion of oral squamous cell carcinoma (OSCC) cells has been reported [64].…”
Section: Caf-evmentioning
confidence: 99%
“…Galectin-1 originating from CAFs in gastric cancer promotes proliferation, migration, and tube formation of vascular endothelial cells and enhanced tumor angiogenesis in vivo [ 43 ]. The upregulation of WNT2 in colorectal CAFs stimulates the migration and invasion of endothelial cells and promotes angiogenesis through the production of pro-angiogenic factors [ 44 ]. VEGF-bound small extracellular vesicles are secreted by CAFs to enhance tumor angiogenesis [ 45 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%